2018
DOI: 10.1080/02699052.2018.1468574
|View full text |Cite
|
Sign up to set email alerts
|

The effect of donepezil on the cognitive ability early in the course of recovery from traumatic brain injury

Abstract: Acute administration of donepezil did not significantly improve measures of cognitive or functional ability beyond that of treatment as usual in patients with moderate-to-severe TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
0
3
0
1
Order By: Relevance
“…These favorable effects on TBI have been reported both in human subjects and in rodent models 62 65 . While not all of the studies have found therapeutic effects, either in rodents or humans 66 , 67 , a body of literature supports their efficacy under some conditions 68 , including demonstration in a double-blind placebo-controlled study of donepezil 69 .…”
Section: Discussionmentioning
confidence: 99%
“…These favorable effects on TBI have been reported both in human subjects and in rodent models 62 65 . While not all of the studies have found therapeutic effects, either in rodents or humans 66 , 67 , a body of literature supports their efficacy under some conditions 68 , including demonstration in a double-blind placebo-controlled study of donepezil 69 .…”
Section: Discussionmentioning
confidence: 99%
“…Campbell et al made a retrospective comparison of the effect of donepezil (starting 5 mg daily and increasing to 10 mg daily seven to 10 days after starting treatment) with rehabilitation therapy on cognitive factors during the acute recovery phase of moderate to severe TBI among 129 patients (55 in the donepezil group and 74 in the rehabilitation group). They found that the two groups had no significant differences (Table 1) (36). However, many studies recommend a dose of 5 -10 mg to treat TBI-induced cognitive impairment (58-60).…”
Section: Traumatic Brain Injury Dementiamentioning
confidence: 97%
“…Results showed no significant improvement across a range of standardized memory measures including the subgroup of participants with MS-TBI. 108 The use of donepezil in acute and subacute TBI populations was not supported in a study by Campbell et al, 109 who employed a retrospective longitudinal analysis of nonrandomly prescribed donepezil with 55 participants with MS-TBI compared with 74 controls receiving standard TBI treatment. No significant differences were found on standardized memory measures or on the Disability Rating Scale or Functional Independence Measure scores.…”
Section: Memory #5: Group-based Interventions May Be Considered For T...mentioning
confidence: 99%